2017
DOI: 10.14218/jcth.2017.00007
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Hepatitis C Virus Treatment in Liver Transplant Candidates in the Era of Direct-acting Antiviral Agents

Abstract: Chronic hepatitis C virus (HCV) infection remains the leading indication for liver transplantation (LT) in the United States. While most patients with chronic HCV infection remain asymptomatic, up to one-third develop progressive liver disease resulting in cirrhosis. LT is often the only curative treatment once significant hepatic decompensation develops. However, antiviral therapy for HCV infection has advanced markedly in the past 5 years with the discovery and approval of direct-acting antiviral agents. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…24,29 Pretransplant patients who are pre-cirrhotic or who have well-compensated disease may benefit from early HCV treatment with stabilization or regression of chronic liver disease, potentially avoiding LT entirely. Ahmed et al recently reported a Markov analysis comparing delayed or immediate HCV treatment among patient waiting for LT. 30 The benefit of HCV treatment varied according to clinical condition.…”
Section: Discussionmentioning
confidence: 99%
“…24,29 Pretransplant patients who are pre-cirrhotic or who have well-compensated disease may benefit from early HCV treatment with stabilization or regression of chronic liver disease, potentially avoiding LT entirely. Ahmed et al recently reported a Markov analysis comparing delayed or immediate HCV treatment among patient waiting for LT. 30 The benefit of HCV treatment varied according to clinical condition.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is limited data regarding the optimal time to initiate DAAs in the liver transplant population. 42,43 A study by Gorgen et al sought to answer this question among 516 patients with underwent LT for HCV with concomitant HCC who received DAA therapy either pre or post-LT. 44 The investigators reported an SVR rate of 93.4% and a 5-year RFS of 93.4% for patients who received DAAs pre-LT and an SVR rate of 96.5% and a recurrence rate of 2.9% for those who received DAAs post-LT. However, the study time period included patients from 2005 to 2015, while DAAs were only widely disseminated in 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is limited data regarding the optimal time to initiate DAAs in the liver transplant population 42,43 . A study by Gorgen et al sought to answer this question among 516 patients with underwent LT for HCV with concomitant HCC who received DAA therapy either pre or post-LT 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Those with MELD scores between 16 and 20 require individualized treatment regimens regarding when to initiate DAA given the potential to precipitate liver failure or other complications with antiviral therapy. DAA therapy in those with MELD > 20 has been shown to have optimal benefit when initiated following liver transplantation at the earliest point of clinical stability (2 - 4 weeks post-transplant) [ 94 , 95 ].…”
Section: Hcvmentioning
confidence: 99%